Numerical Simulation of Effluent Discharges Applications with OpenFOAM (Taylor & Francis, 2023)
Discharge Modeling; Numerical Analysis; Desalination; Outfall; Inclined Jets; OpenFOAM; Effluent Dilution Modeling
English
Keywords: Civil engineering, surveying & building; Mechanical engineering; Water supply & treatment; Discharge Modeling; Numerical Analysis; Desalination; Outfall; Inclined Jets; OpenFOAM; Effluent Dilution Modeling